Fischer aminocarbene complexes of chromium and iron: Anomalous electrochemical reduction of p-carbonyl substituted derivatives - Hoskovcová, Irena; Zvěřinová, Radka; Roháčová, Jana; Dvořák, Dalimil; Tobrman, Tomáš; Záliš, Stanislav; Ludvík, Jiří (Electrochimica acta, 2011)
This contribution shows how a small change of a remote substituent (COOCH 3 for e.g. OCH 3) on Fischer aminocarbene complexes can change totally the LUMO location, and thus electron distribution, extent of π-electron delocalization and, consequently, redox properties of these potential catalysts. During investigation of redox properties of extended series of title compounds, an exceptionally positive reduction potential was observed (non fitting the LFER plot) for p-COOR substituents. This effect is caused by a strong intramolecular electronic interaction, which is specific for p-phenylene dicarbonyl compounds. In this context, the CN bond in aminocarbene moiety has a double bond character and resembles carbonyl function. The interpretation was proved by DFT calculations.